PERANCANGAN DAN PEMBUATAN SOFTWARE DIGITAL SIGNAGE MENGGUNAKAN LED RGB BERBASIS RASPBERRY PI - Sappe Turnip; Hamid Azwar (Politeknik Caltex Riau, 2021)
Digital signage is a digital information board whose function is to replace conventional information boards, digital signage can contain digital information such as text, images and video. Nowadays digital signage has been widely developed as an information medium. such as prayer schedule information, advertising media and expression speech. The use of computers for digital operation there are still some drawbacks such as large device sizes and expensive realtive prices, therefore micro-computer use such as raspberry pi for its operation. Micro computers are more practical to use because of their small size and relatively cheaper price than ordinary computers. The result of designing this digital signage system uses two types of systems, namely offline system (localhost) and online system (Web Hosting). The results of the study showed a presentation value of 100% for black box testing in all input fields. RAM usage when using online systems is quite high compared to ram usage when using offline systems, the average use of online system RAM is 476.73 MB while ram usage for offline systems is 395.3 MB. CPU load when using Offline system increased by an average value of 54.45% while CPU load usage on online systems was smaller with an average value of 43.26%. For online systems.